(untitled) - Grob, Bernard (New York, 1984)
It includes new problems and questions at the end of each chapter, sidebar features throughout the text, and a critical thinking component. The new full-color design makes it easy for students to read circuit diagrams and other important visuals. HyperGraphics, an interactive multimedia program designed to correlate with Glencoe electronics texts, is available for Grob: Basic Electronics.
Keywords: Electronics,Điện tử